Numismatic iconography over two evidences of sigillata hispanica from the roman town of Los Bañales (Uncastillo, Zaragoza) - Javier Andreu Pintado (Sagvntum, 2012)
The following paper presents two new evidences of hispanic sigillata from the roman city of Los Bañales (Uncastillo, Zaragoza), in the center of the Vascones area, that show decorations done with Marcus Aurelius’ coins. Both evidences are analyzed in the context of this habit in the spanish productions of pottery in Tricio firstable in Flavian times and then, briefly, during II century AD. The reflection goes, also, on a interpretative study of the phaenomenon testified in the hispanic sigillata in the first years of Marcus Aurelius and Lucius Verus’ reign offering a plausible explanation of its reasons.